Genomic profile in gestational and non-gestational choriocarcinomas - Mello, Julia Bette Homem de; Ramos Cirilo, Priscila Daniele; Michelin, Odair Carlito [UNESP]; Custódio Domingues, Maria Aparecida [UNESP]; Cunha Rudge, Marilza Vieira [UNESP]; Rogatto, Silvia Regina [UNESP]; Maestá, Izildinha [UNESP] (Elsevier, 2017)
Introduction Gestational (GC) (derived from the placenta) and non-gestational (NGC) choriocarcinomas are trophoblastic diseases originated from abnormal proliferation of trophoblastic cells. These rare tumors share similar morphology and pathological features and differ on chemotherapy response, genetic origin and prognosis. In this study, the genomic profile of choriocarcinomas was performed according to their origin (GC or NGC) aiming to better understand these poorly characterized diseases. Methods Thirteen patients were included in this study; 10 presented previous history of hydatidiform mole and six developed metastasis. Twelve polymorphic microsatellite markers (D15S659, APOC2, D5S816, BAT25, D3S1614, D3S1311, D1S1656, APC-D5S346, D3S1601, D18S70, D8S1110 and D11S1999) were investigated to distinguish GC from NGC. All choriocarcinomas were evaluated by copy number alterations using array CGH. Results Eight cases were classified as GC and five as NGC. Although potentially polymorphic, NGC exhibited significant gain of 21p11. Rare copy number alterations (CNA) were detected as a frequent event in GC including gains of 1p36.33-p36.32 (3 cases), 17q25.3 (4 cases), and losses of 9q33.1 (5 cases), 17q21.3 (3 cases) and 18q22.1 (4 cases) (varying from 724 to 3,053 Kb). Discussion Two tumor suppressor genes are candidates to be involved in GC: TRIM32 (9q33.1) and CDH19 (18q22.1). Gains of CBX2, CBX4 and CBX8 were frequently found in high risk prognostic score in GC. The in silico functional interaction analysis revealed the involvement of PTEN and PI3K-Akt signaling pathways. These data pointed out significant genomic alterations in GC, opening new avenues to better characterize the pathobiology of this disease.
Keywords: Array comparative genomic hybridization; Copy number alteration; Gestational choriocarcinoma; Microsatellites; Non-gestational choriocarcinoma